1997
DOI: 10.1289/ehp.97105s61411
|View full text |Cite
|
Sign up to set email alerts
|

Radon exposures in a Jerusalem public school.

Abstract: In December 1995, ambient radon levels exceeding 10,000 Bq/m3 were measured in a basement shelter workroom of a multilevel East Talpiot, Jerusalem, public elementary school (six grades, 600 students). The measurements were taken after cancers (breast and multiple myeloma) were diagnosed in two workers who spent their workdays in basement rooms. The school was located on a hill that geologic maps show to be rich in phosphate deposits, which are a recognized source for radon gas and its daughter products. Levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There have been a number of studies in other countries which have shown that, in such areas, raised radon levels are also found in schools [2][3][4][5][6][7][8][9]. Raised radon levels have also been found in schools in Cornwall, and Gregory and Stephen [10] have reported case studies of mitigation work which successfully reduced such levels in two primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies in other countries which have shown that, in such areas, raised radon levels are also found in schools [2][3][4][5][6][7][8][9]. Raised radon levels have also been found in schools in Cornwall, and Gregory and Stephen [10] have reported case studies of mitigation work which successfully reduced such levels in two primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…Decision making about policy implementation has been an integral part of these programmes and questions have been raised about the economic implications of the regulations (Clark et al 1981, ICRP 1983Wrixon et al 1988, Colgan and Gutierrez 1995. Very few attempts to answer the economic questions related to proposed and adopted policies for schools remediation have been made, though several authors have suggested possible hypotheses (Richter et al 1997).…”
Section: Introductionmentioning
confidence: 99%